2012
DOI: 10.1016/j.ijengsci.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

On the asymptotic expansion treatment of two-scale finite thermoelasticity

Abstract: a b s t r a c tThe asymptotic expansion treatment of the homogenization problem for nonlinear purely mechanical or thermal problems exists, together with the treatment of the coupled problem in the linearized setting. In this contribution, an asymptotic expansion approach to homogenization in finite thermoelasticity is presented. The treatment naturally enforces a separation of scales, thereby inducing a first-order homogenization framework that is suitable for computational implementation. Within this framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…This modification reflects the macroscopic observation that as ϵ → 0, the temperature within the material in the vicinity of the contact interface remains approximately equal to falsemml-overlineθ¯c. This explicit enforcement of falsemml-overlineθ¯c, similar to the ideas in , decouples the micromechanical analysis into two phases: Mechanical phase : The macroscopic contact pressure is applied to the two samples within a purely mechanical contact problem to solve for the deformed configuration and thereby resolve the real contact area. Within this setup, all temperature‐dependent material properties are evaluated at falsemml-overlineθ¯c. Thermal phase : On the frozen mechanical configuration with a resolved contact interface, a purely thermal problem is solved where the macroscopic normal heat flux falsemml-overlineh¯ is enforced and the temperature jump falsemml-overlineϑ¯c(I) is measured via .…”
Section: A Two‐phase Self‐consistent Frameworkmentioning
confidence: 52%
“…This modification reflects the macroscopic observation that as ϵ → 0, the temperature within the material in the vicinity of the contact interface remains approximately equal to falsemml-overlineθ¯c. This explicit enforcement of falsemml-overlineθ¯c, similar to the ideas in , decouples the micromechanical analysis into two phases: Mechanical phase : The macroscopic contact pressure is applied to the two samples within a purely mechanical contact problem to solve for the deformed configuration and thereby resolve the real contact area. Within this setup, all temperature‐dependent material properties are evaluated at falsemml-overlineθ¯c. Thermal phase : On the frozen mechanical configuration with a resolved contact interface, a purely thermal problem is solved where the macroscopic normal heat flux falsemml-overlineh¯ is enforced and the temperature jump falsemml-overlineϑ¯c(I) is measured via .…”
Section: A Two‐phase Self‐consistent Frameworkmentioning
confidence: 52%
“…Fish and co-workers presented a generalization of the mathematical homogenization method based on double-scale asymptotic expansion to account for non-linear effects such as plasticity [28] and damage [29] in heterogeneous media. The asymptotic homogenization method was continuously developed and nowadays, it still is a very popular research topic [12,52,15,18,119].…”
Section: Review Of Multiscale Methodsmentioning
confidence: 99%
“…An extensive body of literature is devoted to study this technique among which we refer to Refs. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Reviews of the different multiscale approaches can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%